A Study of Housing Elements and Potential Home Injury Risks in Selected Public Housing Estates in Lagos State, Nigeria - Morakinyo, Kolawole Opeyemi; Taiwo, Richard Oluseyi; Oyediran, Demilade Oyewumi; Badejo, Olufunmilola Opeyemi (CV. Gio Architect, 2025)
In general, injuries have been related to different elements and parts of the home environment. That is home injury is potentially connected with primary parts of the home environment. Home wounds might result from different, simultaneous and united causes including physical, underlying, environmental, conduct, way of life, and social variables. Home injury depicts the sorts of injuries that happen in the home and its prompt environmental elements. This study examined housing elements and potential home injury risks in selected public housing estates in Lagos State, Nigeria with a view to informing design decisions for safer housing. This study aims to explore the housing elements—both architectural and environmental—that may contribute to home injury risks in selected public housing estates in Lagos State. By identifying key risk factors, the study hopes to inform policy interventions and promote safer residential environments. Systematic sampling method was employed to select 315 housing units from 8938 units in 3 purposively selected low-income estates (the largest) for questionnaire administration. Ethical approval and clearance were sought from a recognized research ethics review board/committee. Informed consent will be obtained from all participants and confidentiality and anonymity will be strictly maintained. Findings revealed that housing plays a critical role in public health and wellbeing, especially in rapidly urbanizing cities like Lagos, Nigeria. While public housing estates are established to provide affordable shelter, poor design, substandard construction, and inadequate maintenance may contribute to unintentional injuries at home. Injuries such as falls, burns, electric shocks, and poisoning often go underreported, especially in low-income communities, yet they significantly affect quality of life and productivity. The study recommended Policy and Planning (Integrating injury prevention into housing design standards); Maintenance Protocols (Regular inspections and quick repairs); Community Education (workshops on home safety) and Design Improvements (Use of non-slip materials, better lighting, child-proofing measures. The study concluded by emphasizing the link between poor housing design/maintenance and injury risk, and highlights the need for government and stakeholders to prioritize safe, habitable housing.